(untitled) (European Journal of Marketing and Economics, 2020)
Efforts to alleviate poverty in the world have the most perilous impact in human history. Contrary to the prevailing paradigms in public and private policies, the erosion of poverty remains very shocking. The Islamic finance model tried to present its alternative vision and to participate in international efforts to at least help the poor in Muslim countries. This paper is an essay among others that analyzes the effectiveness of this system based on official data.